(untitled) (SCIENCE TIME JOURNAL, 2026)
Speaking anxiety is a major factor hindering the development of oral communication skills in English as a Foreign Language (EFL) learners. Fear of mistakes, negative evaluation, and low self-confidence often reduce participation in speaking activities. This article examines the causes of speaking anxiety and explores effective classroom strategies to address it, including supportive environments, pair and group work, constructive feedback, communicative activities, and gradual task difficulty. The findings suggest that learner-centered approaches improve students’ confidence, participation, and oral performance. Reducing speaking anxiety is crucial for fostering effective communication in EFL classrooms.